Korupsi pajak dan keadilan perpajakan pada kepatuhan wajib pajak (studi kasus pada kantor pelayanan pajak (KPP) Batu - Mukoffi, Ahmad; Sulistiyowati, Yayuk; Himawan, Sukarno; Kontesa , Karolina (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
Taxpayer compliance is based on the trust in tax officers who are not corrupt and the fairness obtained from paying taxes. Obedient Taxpayers are obedient and fulfill and carry out their tax obligations by the provisions of tax laws and regulations. This study aims to determine the effect of tax corruption and tax justice variables on individual taxpayer compliance. This research was conducted at the Tax Office (KPP) Batu. The type of data used in this research is descriptive quantitative data using purposive sampling method as a data collection technique and distributing questionnaires as a research data collection technique. At the same time, the sample used in this study was 95 individual taxpayers. The study results stated that significantly and partially, the tax corruption variable affected the compliance of individual taxpayers at the Batu Tax Service Office (KPP).